The Influence of Accounting Information Systems on LPD Performance in Buleleng Regency, Bali - Ni Nengah Seri Ekayani; Kadek Nadia Pratiwi Lestari; Kadek Diviariesty (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the influence of accounting information systems on the performance of Village Credit Institutions (LPD) in Buleleng Regency. The accounting information system in this study is measured through three independent variables: understanding of accounting information systems, implementation of accounting information systems, and financial management. The research method used is quantitative with a survey approach using a questionnaire as a data collection instrument. The research sample consisted of 63 LPDs selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression to test the influence of each variable on LPD performance. The results show that understanding of accounting information systems, implementation of accounting information systems, and financial management partially and simultaneously have a significant and positive effect on LPD performance. This finding emphasizes the importance of employee competence in understanding and implementing accounting information systems effectively, as well as the importance of good financial management to improve institutional performance. This research is expected to serve as a reference for LPDs in improving the quality of their performance by strengthening accounting information systems and financial management.